2008
DOI: 10.1074/jbc.m800482200
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based Functional Study Reveals Multiple Roles of Transmembrane Segment IX and Loop VIII–IX in NhaA Na+/H+ Antiporter of Escherichia coli at Physiological pH

Abstract: The three-dimensional crystal structure of Escherichia coli NhaA determined at pH 4 provided the first structural insights into the mechanism of antiport and pH regulation of a Na ؉ /H ؉ antiporter. However, because NhaA is activated at physiological pH (pH 6.5-8.5), many questions pertaining to the active state of NhaA have remained open including the structural and physiological roles of helix IX and its loop VIII-IX. Here we studied this NhaA segment (Glu 241 -Phe 267 ) by structure-based biochemical approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(78 citation statements)
references
References 48 publications
5
73
0
Order By: Relevance
“…In a recent study (27), we used scanning Cys replacements for intermolecular cross-linking and identified amino acid residues that participate in the NhaA dimer interface at the cytoplasmic side of the membrane: (i) Residues Ser 246 and Pro 247 at the junction between TMS IX and loop VIII-IX and (ii) L255 inside TMS IX. As predicted by the electron spin resonance based model of the NhaA dimer (14), the residues that cross-link efficiently cluster on one face of TMS IX, Table S1, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study (27), we used scanning Cys replacements for intermolecular cross-linking and identified amino acid residues that participate in the NhaA dimer interface at the cytoplasmic side of the membrane: (i) Residues Ser 246 and Pro 247 at the junction between TMS IX and loop VIII-IX and (ii) L255 inside TMS IX. As predicted by the electron spin resonance based model of the NhaA dimer (14), the residues that cross-link efficiently cluster on one face of TMS IX, Table S1, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mutants P247C, A248C,and L255C were described previously in Ref. 27. The double mutant ⌬(P45-N58)-L255C was obtained on a pCL-AXH3 background by ligating the BglII-MluI fragment (682 bp) with BglII-MluI fragment (4.08 kb) of plasmid pCL-AXH3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 10 single-cysteine variants of sodium:proton antiporter NhaA TM9 are known to form dimers without cross-linking reagents, and the positions forming dimers are located at the N-terminal half of NhaA TM9 (43). Pulsed electron paramagnetic resonance distance measurements of NhaA demonstrated that the TM9s of each protomer of NhaA are close to each other (22).…”
Section: Vol 191 2009 Cysteine Scanning Of Tm3 Of Aspt 2127mentioning
confidence: 99%
“…4b). Our previous MTSET accessibility test of Cys replacements in TMS IX also showed that the cytoplasmic funnel deepens into the membrane at physiological pH as compared with acidic pH (48).…”
Section: Tms II Bears Conserved Residues Of Which Cys Replacementmentioning
confidence: 99%